دراسة تحليلية لقصة "دموع الأمير" لنجيب الكيلاني - Robina Naz (Pakistan Journal of Islamic Research)
The short story is considered one of the best literary arts and has a special impact in minds. From all literary arts, it is the closest to human nature. It is such an arts which withdraws its elements from the bitterness and sweetness of everyday life and dismantles life experiences and feelings. Thus it is a way to elaborate feelings and emotions. Najeeb Gillani is one of the elegant Muslim writers, who devoted himself for religion and made the Islamic tradition the centre of his writing. “Damoo ul Ameer” (Prince’s tears) is one of his popular works. This is a collection of 12 stories which are based on important historical events and historical figures. In this article I will summaries one of the story taken from above mentioned collection with the same title, prince’s tears. I will discuss Najeeb’s life history shortly and then will present summary, critical analysis and technical elements of the story. At the end I will conclude my discussion on the story.